Code Choices in Islamic Forum (Liqo) for Women in Ciamis Regency West Java - Reni Rahayu; Djatmika Djatmika; Sumarlam Sumarlam (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
The study aims to describe code variations and their functions in Islamic Forum (liqo) for women in Ciamis Regency, West Java. Source of data was utterances of murrobbi (speaker) and audiences. This research used a descriptive method. The results are as follows. First, the study found six variations of codes including Arabic, English, Sundanese, Indonesian, code-switching and code-mixing. Second, the research indicates the functions of using those codes including to introduce Arabic terms, to learn Islam through Arabic, to gain prestige, to introduce popular terms, to feel pride, to give familiarity, to show identity, to smooth communication, to maintain Sundanese bond, to unify local language, to quote other sources, to explain speech content, to reiterate the meaning of speech content, and to ease communication. Based on the results, it can be concluded that the two most frequently used codes in Islamic Forum (liqo) for women in Ciamis Regency are Arabic and Indonesian.